Analisis sikap konsumen terhadap keputusan pembelian mobil Pic-up merek Isuzu Panther dan Mitsubishi L300 di Pekanbaru - Frans, Surya; Nursanti, Aida; ', Samsir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is motivated by the many large companies both in the processing of crude oil , palm oil or paper processing industries located in the Riau Province , so that requires a four-wheel transportation especially kind of pick up to support the activities of the company. Of the varioustypes of pick- ups , brand Mitsubishi L - 300 and Isuzu Panther the most interesting. This study aimed to analyze the attitudes of consumers toward purchasing decisions Mitsubishi L300 pick- upsand Isuzu Panther by product , price , promotion and distribution of each pickup. After a literature review , and preparation of hypotheses , data were collected through questionnaire method against 74 respondents consisting of 37 respondents of Isuzu Panther and 37 respondents of Mitsubishi L300. The technique used in this sampling is purposive sampling where the sample is taken with certain considerations and dealing with the problems studied as a pick -up car owners who live in Pekanbaru and who do service reset at each dealer. After that. Do theanalysis is includes Test Validity , Test The reliability and testing hypotheses through two different test samples were not Connect ( Independent Samples T Test ). The results showed that significant differences in consumer attitudes towards purchase decision pickup Isuzu Panther and Mitsubishi L300 based on products variable and known that the product of Isuzu Panther is better than the Mitsubishi L300. For price variable, promotion , and distribution of the results showed that there were no significant differences in consumer attitudes towards buying decision Isuzu Panther and Mitsubishi L300. The results were obtained for the Mitsubishi L300 is cheaper than Isuzu Panther and better product distribution when compared to the Isuzu Panther. However for promotion, Isuzu Panther is superior.Keywords : Consumer Attitudes, Distribution, Price, Product, Promotion, Purchase Decision